2020
DOI: 10.1093/cid/ciaa1219
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz Pharmacogenetics and Weight Gain Following Switch to Integrase Inhibitor–Containing Regimens

Abstract: Background Unwanted weight gain affects some people living with HIV who are prescribed integrase strand transfer inhibitors (INSTI). Mechanisms and risk factors are incompletely understood. Methods We utilized two cohorts to study pharmacogenetics of weight gain following switch from efavirenz- to INSTI-based regimens. In an observational cohort, we studied weight gain at 48 weeks following switch from efavirenz- to INSTI-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 35 publications
3
47
0
Order By: Relevance
“…A separate analysis of data that included ACTG 5202 results found that CYP2B6 genotype predicted weight change from EFV, with higher EFV levels suppressing weight, which will be discussed in more detail later [ 37 ]. Relevant to NRTI considerations, the association was present only when EFV was combined with TDF and not when combined with ABC.…”
Section: Tenofovir Alafenamidementioning
confidence: 99%
See 1 more Smart Citation
“…A separate analysis of data that included ACTG 5202 results found that CYP2B6 genotype predicted weight change from EFV, with higher EFV levels suppressing weight, which will be discussed in more detail later [ 37 ]. Relevant to NRTI considerations, the association was present only when EFV was combined with TDF and not when combined with ABC.…”
Section: Tenofovir Alafenamidementioning
confidence: 99%
“…Investigators assessed weight gain 48 weeks after switch from EFV to an INSTI in 2 cohorts (61 individuals from an observational cohort and 462 from a clinical trial cohort) and evaluated whether the CYP2B6 and UGT1A1 genotypes were associated with weight change following the ART switch (both genotypes are associated with ART metabolism and drug levels) [ 37 ]. Interestingly, the results demonstrated that CYP2B6 EFV slow metabolizers experienced significantly greater weight gain after the switch from EFV to EVG or RAL, but not DTG.…”
Section: Integrase Strand Transfer Inhibitorsmentioning
confidence: 99%
“…There is growing research regarding pharmacogenetics predicting weight gain or loss with specific ARVs. In a retrospective investigation, patients with CYP2B6 polymorphisms (slow metabolizers of EFV) gained more weight following a switch from an EFV- to INSTI-based regimen, potentially reflecting withdrawal of the inhibitory effect of higher EFV concentrations on weight gain [ 20 ]. Conversely, patients with CYP2B6 genotypes associated with extensive metabolism of EFV experienced similar weight gain with EFV-based ART as patients with an INSTI-based regimen [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, similar to several previous reports [ 1 , 4 , 9 , 12 ], our findings show that INSTI users had greater weight gain than NNRTI users, even though the most prevalent INSTI in our study was elvitegravir, which was associated with less weight gain than dolutegravir or bictegravir [ 1 , 9 ]. These findings may partly be explained by the effect of efavirenz on weight suppression as efavirenz accounted for 93% of NNRTIs in this study [ 27 , 28 ]. Our results did not, however, support the hypothesis that the greater weight gain caused by INSTI was due to a more rapid return-to-health effect.…”
Section: Discussionmentioning
confidence: 99%